Capital market development and economic growth: an ARDL approach for Saudi Arabia, 1985–2018 - Algaeed, Abdulaziz Hamad (Journal of Business Economics and Management, 2021)
The aim of this paper is to analyze and test the effects of capital market development on the per-capita GDP growth in Saudi Arabian economy covering the period of 1985-2018. An ARDL, FMOLS and Johansen tests are implemented. The stock market indicators: share price index, capitalization, liquidity, number of share transactions, and number of shares are employed using a log-linear eclectic model designed to fit the availability of data. Capitalization and liquidity came up with negative signs, contrary to the findings of lots of studies in economic literature. However, the share price index, number of shares traded, and the ratio of number of share transactions had the right signs as expected a priori. The findings raise serious questions about the size of the market, the steps and efforts that have been taken to deepen the capital market and their consequences on the function and potency of capital market in fostering per-capita GDP growth. Applying Granger causality test, share price index, market capitalization and number of shares traded do not granger cause per-capita GDP. They are significant at 5 percent level. Capital market authority (CMA) should draw a road map to accelerate deepening the capital market in order to serve economic growth. First published online 23 December 2020